Kajian Kinerja Pembangkit dan Emisi Gas Buang dari Kegiatan Co-Firing Menggunakan Tongkol Jagung di PLTU Sumbawa Barat - Ariwibawa, Yunisetya; Brunner, I Made Indradjaja (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Co-firing activities have been implemented at the Sumbawa Barat Power Plant (PLTU), which has a capacity of 2 x 7 MW and is operated by PT PLN UPK Tambora. The power plant uses a stoker type boiler fired with low calorific coal and biomass. The biomass used for co-firing is corn cobs, which are readily available in the vicinity of the power plant. The co-firing process involves combining 3% dried corn cobs with 97% coal. The mixture is first prepared manually at the dry coal site. The mixture is then processed through a crusher to ensure a uniform particle size. Finally, the ground mixture is fed into the boiler room via a coal feeder. Key generator metrics are monitored, including coal flow, total air flow, furnace exit gas temperature, furnace exit pressure, main steam temperature, and main steam pressure. In addition, air quality emissions, specifically the levels of SO2 and NOx in the flue gas, are being monitored. The co-firing activity, conducted over a 3-hour period, showed that the operating parameters of the generator did not undergo significant changes and remained suitable for the safe operation of the power plant. In addition, the levels of SO2 and NOx in the flue gas decreased compared to the use of 100% coal.